Fabrication of transparent NiTe2 electrodes via magnetron sputtering combined with chemical exfoliation - Lee, Sung Hyuk; Kim, Se Yun; Kim, Seung Min; Jeong, Jae Im; Kim, Suk Jun (ELSEVIER SCIENCE SA, 2017)
Transparent conductive NiTe2 electrodes have been fabricated via magnetron sputtering followed by chemical exfoliation. The freshly deposited NiTe2 thin films with thicknesses of 9 nm exhibited an electrical resistivity of 82 mu Omega cm and transparency of 53%, which were further increased by chemical exfoliation up to 289)162 mu Omega and 61% (70% at a wavelength of 285 nm), respectively. The thin films obtained by sputtering an intermetallic NiTe2 target were characterized by lower electrical resistivity as compared to that of the films fabricated by co-sputtering of Ni and Te targets, which could be attributed to the larger number of grains with the out-of-plane c-axis orientation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: TRANSITION-METAL DICHALCOGENIDES; THIN-FILMS; EPITAXIAL-GROWTH; GRAPHENE; MOS2; CONDUCTIVITY; DEPOSITION; EFFICIENCY; COMPOSITE; NETWORKS